Arterial Hypertension and Tyrosine Kinase Inhibitors in Chronic Myeloid Leukemia: A Systematic Review and Meta-Analysis - Mulas, Olga; Caocci, Giovanni; Mola, Brunella; La Nasa, Giorgio (Frontiers in Pharmacology, 2021)
Background: Off-target effects in chronic myeloid leukemia (CML) patients treated with Tyrosine kinase inhibitors (TKI) are associated with cardiovascular toxicity. Hypertension represents an important cardiovascular complication and, if not appropriately managed, can contribute to develop thrombotic events. Third generation TKI ponatinib is associated with hypertension development and its use is more restricted than the past. Few data are reported for second generation TKI, nilotinib, dasatinib and bosutinib. The aim of this paper was to evaluate with a systematic review and meta-analysis the real incidence of hypertension in CML patients treated with second or third generation TKI Methods: PubMed database, Web of Science, Scopus and ClinicalTrials.gov were systematically searched for studies published between January 1st, 2000 to January 30st, 2021; the following terms were entered in the database queries: Cardiovascular, Chronic Myeloid Leukemia, CML, Tyrosine kinases inhibitor, TKI, Hypertension. The study was carried out according to the Preferred Reporting Items for Systematic and Meta-analyses (PRISMA) statement. Results: Pooled analysis of hypertension incidence was 10% for all new generation TKI, with even a higher prevalence with ponatinib (17%). The comparison with the first generation imatinib confirmed that nilotinib was associated with an increased significant risk of hypertension (RR 2; 95% CI; 1.39-2.88, I2=0%, z=3.73, p=0.0002). The greatest risk was found with ponatinib (RR 9.21; 95% CI; 2.86-29.66, z=3.72, p=0.0002). Conclusion: Hypertension is a common cardiovascular complication in CML patients treated with second or third generation TKI.